Religious Values Included in Islamic Education Textbooks for Fifth, Sixth, and Seventh Grades in Palestine - Roqaya Arar (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to reveal the degree of inclusion of religious values ​​in Islamic education textbooks in Palestine, by analyzing the content of those textbooks, as the study used a descriptive analytical method. The tool of the study was a list of religious values, which included three areas, and which was applied to a sample of three textbooks of Islamic education. By statistical treatment of the data, the results of the study reveal the availability of religious values ​​to varying degrees in the Islamic education textbooks for the fifth, sixth, seventh grades, where the field of belief values ranked first, with a high percentage, and the field of social values ranked second at a low rate, and the field moral values came in third place, with a low percentage. The study recommends conducting more studies to identify religious values ​​in other textbooks and stages of study to provide informed feedback for review of textbooks.